Forward Hedging and Vertical Integration in Electricity Markets. - Chemla,G; Porchet,A; Touzi,N; Aïd,R (2009)
This paper analyzes the interactions between vertical integration and (wholesale)spot, forward and retail markets in risk management. We develop an equilibriummodel that fits electricity markets well. We point out that vertical integration andforward hedging are two separate levers for demand and spot price risk diversification.We show that they are imperfect substitutes as to their impact on retail prices andagents’ utility because the asymmetry between upstream and downstream segments.While agents always use the forward market, vertical integration may not arise. Inaddition, in presence of highly risk averse downstream agents, vertical integration maybe a better way to diversify risk than spot, forward and retail mar kets. We illustrateour analysis with data from the French electricity market.